The Origins of the Narrative Structures in the Chansons de Geste : Methodological Notes on Joël Grisward’s comparativism - Andrea Ghidoni (Perspectives Médiévales)
The research by Joël Grisward on the chansons de geste has involved an important component in the formation of medieval heroic legends, i.e. the folkloric element; his studies describe the reactivation of the Indo-European trifunctional scheme – according to Georges Dumézil’s theories - that Grisward tries to extrapolate from the narrative structure. It is necessary to understand the underlying pattern of Grisward’s work, then to reflect on his method. The present rethinking of the model by Grisward will use two conceptual and epistemological tools active in other fields: the first one is borrowed from the unpublished notes on Germanic legends drafted by Saussure; the second one is the concept of polythetic category formulated by Rodney Needham in an anthropological context, conception partly borrowed from similar reflections in the field of natural sciences.